2018
DOI: 10.3389/fimmu.2018.01531
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Cooperation Between P2Y2 and P2X7 Receptors Promote Cutaneous Leishmaniasis Control: Involvement of Pannexin-1 and Leukotrienes

Abstract: The release of damage-associated molecular patterns, including uridine triphosphate (UTP) and adenosine triphosphate (ATP) to the extracellular milieu is a key component of innate immune response to infection. Previously, we showed that macrophage infection by the protozoan parasite Leishmania amazonensis—the etiological agent of cutaneous leishmaniasis—can be controlled by ATP- and UTP-mediated activation of P2Y and P2X7 receptors (activated by UTP/ATP and ATP, respectively), which provided comparable immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…Previously, we showed that antiparasite effects attributed by UTP and ATP involve P2X7R and PANX-1 channels in infected macrophages [ 19 ]. We also reported that antiparasitic immune responses triggered by the ATP/P2X7R/PANX-1 axis require NLRP3 inflammasome activation in macrophages infected with L. amazonensis [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we showed that antiparasite effects attributed by UTP and ATP involve P2X7R and PANX-1 channels in infected macrophages [ 19 ]. We also reported that antiparasitic immune responses triggered by the ATP/P2X7R/PANX-1 axis require NLRP3 inflammasome activation in macrophages infected with L. amazonensis [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the host defense mechanisms that are modulated to control parasite replication and treat the disease are not thoroughly characterized, and several aspects of the disease remain poorly understood [ 25 ]. We previously reported the involvement of purinergic receptors, including P2Y 2 R and P2X7R, in the control of L. amazonensis infection in vitro and in vivo [ 4 , 19 ]. These receptors induce the activation of several microbicidal mechanisms in host cells during infection (i.e., NO, ROS, LTB 4 production) [ 20 , 21 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations